Lecturers and full time diploma students perceptions on the effectiveness of recycle campaign/ Hasnah Saini… [et.al.] - Saini, Hasnah; Md Yusoff, Muhdiya; Azmi, Noor Hidayah; Mamat, Rosmawati (2005)
The study of Lecturers and Full Time Diploma Students Perception on the Effectiveness of Recycle Campaigns in our campus is designed goal to investigate whether the recycle activities in UiTM has good response or vice versa from the UiTM’s citizens. The objective of this study also is to enhance them awareness among the UiTM citizens about the importance of recycle activities. Furthermore, it is also to ensure a beautiful and cleanliness surrounding in our campus would be protected. Besides, it is to provide good image by the others towards UiTM. Besides that, the result gained can be used as guidelines to improve the effectiveness and efficiency of recycle activities in our campus. At the same time, based on the survey made, it will help to improve the recycle campaigns to be more attractive and effective.